Respuesta :

Answer:

Step-by-step explanation:

3

2

2

3

y+

3

1

y+4=0

Combine −

2

3

y and  

3

1

y to get −

6

7

y.

3

2

6

7

y+4=0

Convert 4 to fraction  

3

12

.

3

2

6

7

y+

3

12

=0

Since  

3

2

 and  

3

12

 have the same denominator, add them by adding their numerators.

3

2+12

6

7

y=0

Add 2 and 12 to get 14.

3

14

6

7

y=0

Subtract  

3

14

 from both sides. Anything subtracted from zero gives its negation.

6

7

y=−

3

14

Multiply both sides by −

7

6

, the reciprocal of −

6

7

.

y=−

3

14

(−

7

6

)

Multiply −

3

14

 times −

7

6

 by multiplying numerator times numerator and denominator times denominator.

y=

3×7

−14(−6)

Do the multiplications in the fraction  

3×7

−14(−6)

.

y=

21

84

Divide 84 by 21 to get 4.

y=4

Answer:

Step-by-step explanation:

Divide 84 by 21 to get 4.

y=4